miR-210 loss leads to widespread phenotypic and gene expression changes in human 293T cells - Zhang, Xiaoxiao; Meng, Zhen; Yang, Chengyong; Wang, Chenghao; Zhang, Kexin; Shi, Anxin; Guo, Jingjing; Feng, Yong; Zeng, Yan (Frontiers in Genetics, 2024)
IntroductionHypoxia responses are critical for myriad physiological and pathological processes, such as development, tissue repair, would healing, and tumorigenesis. microRNAs (miRNAs) are a class of small non-coding RNAs that exert their functions by inhibiting the expression of their target genes, and miR-210 is the miRNA universally and most conspicuously upregulated by hypoxia in mammalian systems. For its relationship to hypoxia, miR-210 has been studied extensively, yet no consensus exists on the roles and mechanisms of miR-210 in human physiological processes or diseases, and we know little about genuine miR-210 target genes in humans.MethodsTo better investigate the functions and mechanisms of human miR-210, therefore, we derived the human miR-210 gene knockout (KO) 293T cell lines using the CRISPR/Cas9 technology. We then examined the cellular phenotypes and gene expression profiles of 293T cells under normoxia and hypoxia conditions.Results and DiscussionWe found that the loss of miR-210 altered a variety of cellular phenotypes including proliferation and apoptosis. Subsequent global gene expression analyses identified plausible mechanisms underlying these phenotypic changes in 293T cells. In particular, we showed that miR-210 might target the expression of BNIP3L as a potential mechanism to suppress apoptosis. Surprisingly, the mRNA levels of most previously reported miR-210 target genes were not induced upon miR-210 KO, suggesting a need to reexamining and studying human miR-210 functions directly and comprehensively. Thus, our work established a human cellular system and opportunity to unravel the complexity of the regulatory networks by miR-210.